Developing a drama-based inclusive education workshop about disability for pre-service teachers: a narrative inquiry after Scheler and Levinas. Issue 5 (29th July 2022) - Raphael, Jo; Creely, Edwin; Moss, Julianne
ABSTRACT: A problem in teacher education is how to make learning about inclusive education meaningful so that it is more than just another idea for pre-service teachers to study and has deep and lasting effects on their practice as educators. One innovative approach developed at Deakin University is the provision of the Teaching for Diversity Workshop, involving a series of embodied drama-based activities, in which pre-service teachers encounter issues of inclusion and disability through working with not only academics but also people with disabilities, who become their lead teachers and mentors. This article is about the development and enacting of this with actors from Fusion Theatre in Melbourne, Australia. This article, through the voice of its creator, Jo Raphael, details a series of narrative vignettes that were selected following conversations between the co-authors as they reflected on the workshop as a learning encounter. Using the ideas of "fellow-feeling" from Max Scheler and "alterity" from Emmanuel Levinas, the article considers the genesis of the workshop and theorises the high level of student engagement and ethical commitment evident in the workshops, including joyful laughter, embodied participation, positive risk-taking, acclamations of beauty and a palpable shift from apprehension at the beginning to high levels of interaction. Thus, there was considerable disruption of students' beliefs about disability as agency was distributed to those with disabilities. It is clear from the data that participatory and embodied approaches in teacher education, including the use of applied drama approaches, are highly effective for overcoming barriers and promoting inclusivity.